Severe hypocalcemia and life-threatening ventricular arrhytmias: case report and proposal of a diagnostic and therapeutic algorithm - Cecchi, Emanuele (Clin Cases Miner Bone Metab, 2015)
Hypocalcemia is frequent in the setting of endocrine disorders, bone diseases and renal failure. When hypocalcemia is severe it can predispose to life-threatening ventricular arrhythmias; in such cases a rapid admission to hospital and a prompt correction of electrolyte imbalance are needed. We report the case of an old patient suffering from renal failure that was admitted to our cardiac step-down unit because of severe hypocalcemia associated with ventricular arrhythmias. Hypocalcemia was promptly treated and an endocrinologic consult was requested for investigating the causes of this electrolyte imbalance. Our experience suggests the creation of a new synergy between cardiologists and endocrinologists that led us to build a simple and schematic algorithm for the diagnosis and treatment of hypocalcemia.